Development of Entry Location Assessment Criteria (ELAC) model for Malaysian construction firms in international markets / Norizzati Ibrahim and Che Maznah Mat Isa - Ibrahim, Norizzati; Mat Isa, Che Maznah (2020)
The construction industry plays a major and important role in transforming the Malaysian construction industry to the international level apart from the domestic level. However, only 0.74% Malaysian construction firms have been involved in international market. Hence, this research focuses on development of Entry Location Assessment Criteria (ELAC) Model based on Malaysian construction firms sustained in international markets. The ELAC formula was derived through a development of taxonomy criteria from previous studies. The construction firms' performance was analyzed and ranked using a weightage score characterized under three (3) dimensions of country with the taxonomy criteria. The ELAC score shows that three (3) construction firms score 66%, 53% and 50% have sustained international operations in various locations by obtaining an ELAC score of more than 50% by venturing to ASEAN countries, developing countries and developed countries. Even though his study is limited to Malaysian construction firms, it provides significant information and contributes to the current knowledge in international market expansion. This ELAC model is useful especially for construction firms that are just beginning to explore foreign business opportunities or for the global players that are expanding geographically to new international markets.